Comparative Analysis of Highland and Lowland Agricultural Commodities Based on Location Quotient (LQ) in South Sumatra Province.pdf: Analisis Komperatif Komoditi Pertanian Dataran Tinggi dan Rendah Berdasarkan Location Quotient (LQ) di Provinsi Sumatera Selatan - Sari, Serly Novita; Ayu Sulastri, Merna; Sudarti, Sudarti; Maryadi, Maryadi; Wahyu Swasdiningrum, Trisna (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2024)
This study examines the comparative advantages of agricultural products from highland and lowland areas in South Sumatra Province using the Location Quotient (LQ) method. The research aims to identify specific commodities that dominate each region and evaluate their potential for regional economic development. Data were collected from agricultural production reports, regional economic statistics, and field surveys. The LQ analysis reveals the agricultural specialization in both highland and lowland regions. Highland areas primarily focus on plantation crops such as coffee and tea, while lowland areas excel in rice production and horticulture. The results indicate that highland commodities have a high LQ value, reflecting their contribution to the regional economy and export potential. Conversely, lowland commodities showcompetitive advantages in meeting local demand and supporting food security. This comparative analysis highlights the importance of tailoring agricultural policies to the unique characteristics of each region. Strategies such as infrastructure development, market access improvement, and sustainable farming practices can enhance productivity and competitiveness. The findings also emphasize the need for diversification and value-added processing to increase income and reduce economic vulnerability in both highland and lowland areas.